Self-assembly of luminescent N-annulated perylene tetraesters into fluid columnar phases1. Issue 18 (14th May 2015) - Gupta, Ravindra Kumar; Pathak, Suraj Kumar; Pradhan, Balaram; Shankar Rao, D. S.; Krishna Prasad, S.; Achalkumar, Ammathnadu S.
<x xml:space="preserve">Abstract</x> Luminescent columnar N-annulated perylene tetraesters.